Genomic characterization and phylogenetic analysis of a novel Nairobi sheep disease genogroup Orthonairovirus from ticks, Southeastern China - Zhang, Xu; Li, Hang-Yuan; Shao, Jian-Wei; Pei, Ming-Chao; Cao, Chong; Huang, Fu-Qiang; Sun, Ming-Fei (Frontiers in Microbiology, 2022)
The increasing prevalence and transmission of tick-borne diseases, especially those emerging ones, have posed a significant threat to public health. Thus, the discovery of neglected pathogenic agents carried and transmitted by ticks is urgently needed. With unbiased high-throughput sequencing, a novel orthonairovirus, Meihua Mountain virus (MHMV), was identified in bloodsucking ticks collected from cattle and wild boars in Fujian province, Southeastern China. The full-length genome was determined by RT-PCR and RACE. Genomic architecture of MHMV shares typical features with orthonairoviruses. Phylogenetic analyses suggested that MHMV is clustered into the NSD genogroup of the genus Orthonairovirus and is closely related to the Hazara virus. The RdRp, GPC, and N protein of MHMV shares 62.3–83.5%, 37.1–66.1%, and 53.4–77.3% amino acid identity with other NSD genogroup viruses, respectively, representing a novel species. The overall prevalence of MHMV in ticks was 16.42% (22/134 tick pools), with 61.1% (11/18) in Haemaphysalis hystricis, 50% (4/8) in Haemaphysalis formosensis, 75% (6/8) in Dermacentor taiwanensis, and 1% in Rhipicephalus microplus (1/100). This study presented the first report of tick carried orthonairovirus in Fujian province and highlighted the broad geographic distribution and high genetic diversity of orthonairoviruses in China.